2015
DOI: 10.3892/br.2015.418
|View full text |Cite
|
Sign up to set email alerts
|

The association between mean platelet volume and chronic atrial fibrillation and the presence of thrombotic events

Abstract: Abstract. Mean platelet volume (MPV), a marker of platelet activation, is a surrogate marker of platelet function and a potential mediator of the association between inflammation and thrombosis. The present retrospective study sought to investigate the association between MPV and the presence of thrombotic events (TEs) in patients with chronic atrial fibrillation (AF). A total of 114 consecutive patients with chronic AF were enrolled from a Chinese hospital. Individuals were divided into three groups: The AF+T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Therefore, MPV may also be a response to infl ammation and thrombosis (9). It has been reported that an exaggerated infl ammatory response is associated with a higher risk of PoAF (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MPV may also be a response to infl ammation and thrombosis (9). It has been reported that an exaggerated infl ammatory response is associated with a higher risk of PoAF (20).…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets have larger volumes and contain wide range of vasoactive substances and prothrombotic factors. Therefore, MPV may also be a response to infl ammation and thrombosis (9). An increased MPV is associated with overall cerebrovascular and cardiovascular mortality rates (10).…”
Section: Introductionmentioning
confidence: 99%
“…There is a positive association between MPV and the severity of acute ischemic stroke [10], and MPV is useful for predicting the risk of ischemic stroke in patients with AF [11-15]. A recent case-control study showed that stroke patients with AF have a higher MPV than AF patients without a stroke history [13].…”
Section: Evidence That the Mpv Is A Biomarker Of Ischemic Stroke Riskmentioning
confidence: 99%
“…A previous study reported abnormal platelet morphology, as well as increased soluble level and total level of platelet P‐selectin during acute IS . Recent studies have revealed that the mean platelet volume could function as a surrogate marker of platelet function and a potential mediator correlating inflammation with thrombosis . Platelet‐derived biomarkers for diagnosis and prognosis of IS are in high demand, but are still limited.…”
Section: Introductionmentioning
confidence: 99%